Increasing Fracture Risk Associates With Plasma Circulating MicroRNAs in Aging People’s Sarcopenia - He, Nana; Zhang, Yuelin; Zhang, Yue; Feng, Beili; Zheng, Zaixing; Wang, Dongjuan; Zhang, Shun; Ye, Honghua (Frontiers in Physiology, 2021)
Aging generally coincides with a gradual decline in mass and strength of muscles and bone mineral density (BMD). Sarcopenia is closely linked to osteoporosis in the elderly, which can lead to abnormal gait, balance disorders, and dysfunctions, as well as increase in the risks of falls, fractures, weakness, and death. MicroRNAs (miRNAs, miRs) are a kind of short and non-coding RNA molecules but can regulate posttranscriptional protein expression. However, we have known little about their participation in age-associated osteoporosis and sarcopenia. The current study aims to confirm those miRNAs as biomarkers for age-related reduction in muscular atrophy associated with human blood fractures. In our study, 10 fracture-risk-related miRNAs (miR-637, miR-148a-3p, miR-125b-5p, miR-124-3p, miR-122-5p, miR-100-5p, miR-93-5p, miR-21-5p, miR-23a-3p, and miR-24-3p) were analyzed. For the initial screening, we determined the abundance of fracture-risk-associated miRNAs by RT-PCR most frequently detected in enrolled 93 elderly with sarcopenia and non-sarcopenia, respectively. Statistically, the relative expression levels of plasma miR-23a-3p, miR-93-5p, and miR-637 in the sarcopenia group were significantly lower than that in the non-sarcopenia group, while the levels of other miRNAs did not change significantly. Moreover, we showed that the levels of ASM/height2, handgrip strength, and 4-m velocity in the sarcopenia group were significantly lower than in the non-sarcopenia group. Whereafter, we expanded the sample for further detection and analysis and revealed that the levels of plasma miR-23a-3p, miR-93-5p, and miR-637 in the sarcopenia group were significantly lower than that in the non-sarcopenia group, which is consistent with the initial screening experiment. From our analysis, changes in levels of plasma miR-93-5p and miR-637 were dramatically related to ASM/height2. Furthermore, changes in miR-23a and miR-93-5p were significantly affected by ASM/height2 in female individuals, with no significant correlations between miRNAs changes and these diagnostic indexes in male individuals after adjusting sex. The study showed that plasma miRNAs changed in an aging-related sarcopenia manner and were associated with increased fracture risk. In aging patients, plasma miR-23a-3p, miR-93-5p, and miR-637 have the potential as biomarkers of sarcopenia, which can affect the development of physiological dysfunction and may be also used in the fracture risk assessment of these patients.